Application of Islamic concept of knowledge in social sciences: the case of International Islamic University Malaysia - Md. Noon, Hazizan (2017)
This paper discusses the implementation of Islamic educational ideals, as rooted in and derived from the very source of Islamic religion namely the Divine revelation, at one of the higher learning institutions in Malaysia namely the International Islamic University Malaysia (IIUM). It has two main parts: the theoretical and the applied. The theoretical part deals with conceptual issues focussing mainly on the formulation of Islamic concept of integrated knowledge which is closely related to the philosophy of Islamic education. The applied part addresses the translation of this concept into practice with particular discussion of the experiment, experience and model of the International Islamic University Malaysia (IIUM). Part I provides preliminary background for the discussion of Part II which is the focus of this paper. In line with the Conference’s requirement, the illustration is tailored towards social sciences with particular elaboration on its implementation by the IIUM’s Department of Sociology and Anthropology.